The Structural and Magnetic Properties of Gadolinium Doped CoFe2O4 Nanoferrites. (6th September 2015) - Lin, Qing; Lin, Jinpei; He, Yun; Wang, Ruijun; Dong, Jianghui
Abstract : Gadolinium substituted cobalt ferrite CoGd x Fe2− x O4 ( x = 0, 0.04, 0.08) powders have been prepared by a sol-gel autocombustion method. XRD results indicate the production of a single cubic phase of ferrites. The lattice parameter increases and the average crystallite size decreases with the substitution of Gd 3+ ions. SEM shows that the ferrite powers are nanoparticles. Room temperature Mössbauer spectra of CoGd x Fe22− x O4 are two normal Zeeman-split sextets, which display ferrimagnetic behavior. The saturation magnetization decreases and the coercivity increases by the Gd 3+ ions.